SITUATIONAL ANALYSIS OF EYE CARE SERVICES IN SOUTH SULAWESI - AULIA, NABITA; Amalius, Ahmad Ashraf; Faisal, Andi Akhmad; Kamaruddin, Muhammad Irfan (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesGlobal initiative, also known as “VISION 2020: the Right to Sight”, suggested that determining thenational target of human resources in eye health substantially reduces avoidable blindness andvisual impairment. Shortage of human resources is currently recognized as one of the mainproblems in achieving progress in eye health services to attain the global initiative. The purpose ofthis study is to analyze the situation of eye services in South Sulawesi. MethodsA descriptive study with a qualitative and quantitative approach was performed through aquestionnaire to ophthalmologists in South Sulawesi Districts and also secondary data fromophthalmologists, ophthalmic nurses, the Indonesian Ophthalmologists Association committee,provincial and district health office staffs Hospital in 2022. ResultsThe total population of South Sulawesi Province in 2022 was 9.07 million people. Human resourcedata showed 116 ophthalmologists (ratio 1:250,000 population), 108 trained ophthalmic nurses(ratio of 10 nurses per 1 million population), 1536 trained instructors, 10.918 posyandu cadres, 5trained eye cadres, and 71 refractionists/optometrists (ratio is 20 persons per 1 million people).There were 7 of 24 regencies/cities that have complete mandatory diagnostic examinationequipment. ConclusionThe ophthalmologist ratio in South Sulawesi is normal, however, their distribution is uneven,necessitating a rise in the number of nurses and optometrists with a balanced distribution.